The Effects of Using Rap Music in ESL Language Learning Classroom - Sarmilan, R Gaijandren (2021)
The objectives of this research was to find out the perception and preference of students and teachers on Rap music being used in English literature classrooms for learning and teaching. The aim of this study was to see whether sixth form students from Penang Free School choose to learn English literature through traditional teaching or through the use of rap music. In this study, the qualitative research design was used, specifically thematic analysis. The study's participants were divided into two groups: experimental and control. A semi-structured interview and a rap song with video about a section of the syllabus were used as instruments. In addition, the data analysis methods used in this study were qualitative. The results revealed that sixth-form students at Penang Free School prefer a balanced approach to learning English literature that includes both traditional and rap music. The English literature teacher at Penang Free School is open to incorporating rap music into the classroom. Based on the findings, the researcher concluded that relying exclusively on musical learning while abandoning conventional methods is not the best approach since rap music is not intended to replace traditional teaching; rather, it is intended to supplement key lessons learned in class.